2020
DOI: 10.3892/etm.2020.9056
|View full text |Cite
|
Sign up to set email alerts
|

Post‑arthroscopic osteonecrosis of the knee: A case report and literature review

Abstract: Post-arthroscopic osteonecrosis is a rare complication of arthroscopic surgery. The present study reported on a case of knee osteonecrosis after arthroscopic surgery. The patient, an 81-year-old male, presented with left knee pain and limited range of motion without any history of trauma. MRI revealed medial meniscus tear. Medial partial meniscectomy was performed using arthroscopy. The pain was found to be relieved due to the operation. However, there was an aggravation of pain after two months post-operative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(52 reference statements)
0
2
0
1
Order By: Relevance
“…Sixteen days after the procedure the patient was positive for SARS-CoV-2. Several authors have previously hypothesized that the arthroscopic procedure could cause osteonecrosis, and called it post-operative or post arthroscopy ON [40,41]. In the author's case report, the two possible causes of osteonecrosis were meniscal tear or arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen days after the procedure the patient was positive for SARS-CoV-2. Several authors have previously hypothesized that the arthroscopic procedure could cause osteonecrosis, and called it post-operative or post arthroscopy ON [40,41]. In the author's case report, the two possible causes of osteonecrosis were meniscal tear or arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology is still not fully understood but studies have suggested that it could be due to heat generated to the subchondral bone from radiofrequency probes or more likely from the increased biomechanical load causing insufficiency fractures within the femoral condyle after partial meniscectomy within the compartment. 6,19 There have also been some case reports of AVN after arthroscopic anterior cruciate ligament reconstruction 10 or patellar osteonecrosis after arthroscopy presumably due to excessive disruption of the anterior fat pad. 3 Osteonecrosis of the femoral head with arthroscopy has been rarely seen and reported.…”
Section: Discussionmentioning
confidence: 99%
“…Das gelegentliche Auftreten eines primär radiologisch nicht sichtbaren Knochenmarködems nach Kniegelenkarthroskopie ist bekannt und wurde erstmals von Brahme et al. 1991 beschrieben [ 4 , 5 ]. Das Ausmaß der Nekrose macht dies jedoch im aktuellen Fall eher unwahrscheinlich.…”
Section: Fallanalyseunclassified